Rapid Automatic Naming (RAN) - Based Reading Intervention for Children with Learning Disabilities - Novianti, Ranti; Nadiyah, Salma; Pratama, Azhar; Santoso, Yoga Budhi; Mustika, Argiasri; Ridwan, Prinanda Gustarina (Department of Special Education, 2024)
In addition to phonology, the cause of reading problems in children with difficulty learning to read can occur due to obstacles in Rapid Automatic Naming (RAN). The purpose of this study is to develop a reading intervention program based on Rapid Automatic Naming for children with reading difficulties. This study uses a qualitative research approach with the method applied in this study is a qualitative descriptive method. A reading intervention program based on Rapid Automatic Naming (RAN) for children with learning difficulties to read that can be used by teachers, parents or those in need in order to help children with learning difficulties in reading. The result of this research is the Rapid Automatic Naming (RAN) based Reading Intervention program.